Recombinant actin-depolymerizing factor of the apicomplexan Neospora caninum (NcADF) is susceptible to oxidation - Baroni, Luciana; Abreu-Filho, Péricles Gama; Pereira, Luiz Miguel; Nagl, Markus; Yatsuda, Ana Patricia (Frontiers in Cellular and Infection Microbiology, 2022)
Neospora caninum is a member of Apicomplexa Phylum and the causative agent of neosporosis, a disease responsible for abortions in cattle. Apicomplexan parasites have a limited set of actin-binding proteins conducting the regulation of the dynamics of nonconventional actin. The parasite actin-based motility is implicated in the parasite invasion process in the host cell. Once no commercial strategy for the neosporosis control is available, the interference in the parasite actin function may result in novel drug targets. Actin-depolymerization factor (ADF) is a member of the ADF/cofilin family, primarily known for its function in actin severing and depolymerization. ADF/cofilins are versatile proteins modulated by different mechanisms, including reduction and oxidation. In apicomplexan parasites, the mechanisms involved in the modulation of ADF function are barely explored and the effects of oxidation in the protein are unknown so far. In this study, we used the oxidants N-chlorotaurine (NCT) and H2O2 to investigate the susceptibility of the recombinant N. caninum ADF (NcADF) to oxidation.